VOWEL PHONEMES - Fahmi Idris; Muhammad Ismail (Politeknik Kampar, 2023)
The existence of word vowel phonemes in all languages, including in Indonesian is very dominant. All words in their internal structure must be found in phonemes. As a result of the existence of a very dominant vowel phoneme, its existence is able to form what is called a phoneme vocal sequence. The application of research theory in connection with efforts to describe vowel series phonemes is based on the linguistic theory of the phonological field of the phonemic subfield. Because the study focuses on the smallest unit of language sounds, namely phonemes. The research implementation is based on three strategic stages, namely:1. provision of data, 2. classification and analysis of data, 3. preparation / writing of reports. The findings of the data are more secondary, so the findings of the data focus on the availability of references, so that the existence of a large Indonesian language dictionary acts as a